Relative Inner Amenability and Relative Property Gamma - Jolissaint, Paul (Mathematica Scandinavica, 2016)
Let H be a proper subgroup of a discrete group G. We introduce a notion of relative inner amenability of H in G, we prove some equivalent conditions and provide examples coming mainly from semidirect products, as well as counter-examples. We also discuss the corresponding relative property gamma for pairs of type II_1 factors NM and we deduce from this a characterization of discrete, icc groups which do not have property (T).